Preparation of weaning foods by replacing plant proteins with egg protein - NAEEM,Muhammad (2022)
Abstract The present study was designed to prepare to wean food by replacing plant proteins with egg proteins. The weaning foods containing 14, 16 and 18% extruded soy proteins were replaced with 0, 25, 50, 75 and 100% egg proteins using whole egg powder. Physicochemical analysis of raw material and weaned products, water activity, bulk density, in vitro study for protein digestibility, color analysis, microbiological analysis, and sensorial evaluation. Protein content significantly (p < 0.05) varied from 13.76% to 19.89% for formulated weaning foods with the highest value in T12. Treatment T5 and T11 exhibited minimum water absorption capacity (1.86 mL/g) and maximum (2.63 mL/g), respectively. Treatment T1 exhibited the highest (0.76 mL/g) values of bulk density, while the treatment T7 and T12 had the lowest values (0.69 mL/g). The maximum in vitro digestibility was observed in treatment T15 (83.8%) while the minimum (65.4%) was observed in treatment T1. The sensorial evaluation results for all the treatments are significantly (p < 0.05) varies with an overall acceptable score. Results indicate that the microbial loads also within acceptable limits. The weaning foods composite animal proteins can be a cost-effective and possible tool to overcome malnutrition among children in developing countries.